THE UNRESOLVED ISSUES AND MODERN VIEW ON ATRIAL FIBRILLATION PATIENTS MANAGEMENT - D. V. Losik; S. A. Bayramova; E. A. Pokushalov; I. L. Mikheenko; V. V. Shabanov; A. B. Romanov (Российский кардиологический журнал)
T he article focuses on the main debating and unresolved issues on atrial fibrillation patients therapy, e.g. anticoagulation, antiarrhythmic, intervention and surgical tactics. The weaknesses and disadvantages are discussed, of the modern conservative and invasive strategies, as of the modern classification of atrial fibrillation; the issues on optimal rhythm control in atrial fibrillation, and early diagnostics. Each of these problems is related to the range of opportunities for better understanding and management.